ANALYSIS OF SERVICE QUALITY, PERCEIVED VALUE AND CUSTOMER SATISFACTION TOWARDS CUSTOMER LOYALTY IN INSURANCE INDUSTRY - CASE STUDY OF PT. SYNERGY ADHI MANUNGGAL - Andhika, Benedictus Widy; Hidayat, Nila Khrisnawati; Pasasa, Linus (Academic Research Centre Services, 2015)
The purpose of this research is to study and analyse the impact of service quality, perceived value and customer satisfaction towards customer loyalty in insurance industry - case study of PT. Synergy Adhi Manunggal. The primary data was obtained by using the questionnaires to 100 customers of PT. Synergy Adhi Manunggal. The data is analysed using Structural Equation Modelling (SEM analysis to test the hypotheses). Finding of this research shows that service quality, perceived value and customer satisfaction towards customer loyal. It will be a great challenge for the PT. Synergy Adhi Manunggal in preparing their strategic plan in maintaining customer loyalty.